Synthesis, Characterization and Antibacterial Activity of Some Fluoroquinolones - Ashokrao, Salunke Ramkrushna (My University, 2021)
The work describes the synthesis, characterization and antibacterial activity of novel fluoroquinolones having a bicyclic endo-nortropine group at the C-7 position. Different Q- acids, that form the core structure of commercially available fluoroquinolones, were used as the starting material. Further, the hydroxy group on the nortropine was substituted with different aliphatic, aromatic and heterocyclic groups to explore their antibacterial activity. Nortropine substituted levofloxacin derivatives gave potential antibacterial activity against Vibrio cholrae and Staphylococcus aureus. Short-chain and chloro-heterocyclic moieties attached at the hydroxy group of the C-7 substituent were effective against Staphylococcus aureus of all the synthesized compounds. The structure-activity relationship was explored using the in silico molecular docking studies.
Keywords: NORFLOXACIN; LEVOFLOXACIN; Q-ACID; TOPOISOMERASE IV; DNA GYRASE; NORTROPINE